2022
DOI: 10.3389/fimmu.2022.975367
|View full text |Cite
|
Sign up to set email alerts
|

Role of the CCL2-CCR2 axis in cardiovascular disease: Pathogenesis and clinical implications

Abstract: The CCL2-CCR2 axis is one of the major chemokine signaling pathways that has received special attention because of its function in the development and progression of cardiovascular disease. Numerous investigations have been performed over the past decades to explore the function of the CCL2-CCR2 signaling axis in cardiovascular disease. Laboratory data on the CCL2-CCR2 axis for cardiovascular disease have shown satisfactory outcomes, yet its clinical translation remains challenging. In this article, we describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 168 publications
0
33
0
Order By: Relevance
“…GPCR ligand binding [60], extracellular matrix organization [61], cytokine signaling in immune system [62], interferon signaling [63], signaling by GPCR [64], neuronal system [65] and platelet activation, signaling and aggregation [66] plays an important role in the schizophrenia. Studies have revealed that SIX1 [67], VIP (vasoactive intestinal peptide) [68], GATA6 [69], FRZB (frizzled related protein) [70], CD40 [71], WT1 [72], PCDHGA3 [73], TFAP2B [74], HFE (homeostatic iron regulator) [75], NKX2-5 [76], IGFBP7 [77], HLA-F [78], CCL2 [79], COL1A2 [80], RUNX1 [81], TFF3 [82], IRX4 [83], NOS1 [84], DKK2 [85], IL18R1 [86], ADAM12 [87], NPPC (natriuretic peptide C) [88], COL1A1 [89], ABCG2 [90], SIX2 [91], CSRP1 [92], MR1 [93], NINJ2 [94], ACE (angiotensin I converting enzyme) [95], TBX1 [96], CTSC (cathepsin C) [97], DLX6 [98], KCNE1 [99], AZGP1 [100], CYP1B1 [101], PRRX1 [102], CD34 [103], A2M [104], CDKN2A [105], SERPINE1 [106], CD44 [107], FABP4 [108], ITGB3 [109], ALOX5AP [110], DAND5 [111], SFRP4 [112], RUNX2 [113], TACR3 [114], MYD88 [115], CYBA (cytochrome b-245 alpha chain) [116], STAT6 [117], FOXC1 [118], FN1 [119], TLR6 [120], CAV1 [121], RGS4 [122], TPM2 [123], TNFSF4 [124], LOX (lysyl oxidase) [125], SMOC2 [126], SPHK1 [127], FOLH1 [128], CYP2C8 [129], CD163 [130], DIRAS3 [131], OSMR (oncostatin M receptor) [132], POSTN (peri...…”
Section: Discussionmentioning
confidence: 99%
“…GPCR ligand binding [60], extracellular matrix organization [61], cytokine signaling in immune system [62], interferon signaling [63], signaling by GPCR [64], neuronal system [65] and platelet activation, signaling and aggregation [66] plays an important role in the schizophrenia. Studies have revealed that SIX1 [67], VIP (vasoactive intestinal peptide) [68], GATA6 [69], FRZB (frizzled related protein) [70], CD40 [71], WT1 [72], PCDHGA3 [73], TFAP2B [74], HFE (homeostatic iron regulator) [75], NKX2-5 [76], IGFBP7 [77], HLA-F [78], CCL2 [79], COL1A2 [80], RUNX1 [81], TFF3 [82], IRX4 [83], NOS1 [84], DKK2 [85], IL18R1 [86], ADAM12 [87], NPPC (natriuretic peptide C) [88], COL1A1 [89], ABCG2 [90], SIX2 [91], CSRP1 [92], MR1 [93], NINJ2 [94], ACE (angiotensin I converting enzyme) [95], TBX1 [96], CTSC (cathepsin C) [97], DLX6 [98], KCNE1 [99], AZGP1 [100], CYP1B1 [101], PRRX1 [102], CD34 [103], A2M [104], CDKN2A [105], SERPINE1 [106], CD44 [107], FABP4 [108], ITGB3 [109], ALOX5AP [110], DAND5 [111], SFRP4 [112], RUNX2 [113], TACR3 [114], MYD88 [115], CYBA (cytochrome b-245 alpha chain) [116], STAT6 [117], FOXC1 [118], FN1 [119], TLR6 [120], CAV1 [121], RGS4 [122], TPM2 [123], TNFSF4 [124], LOX (lysyl oxidase) [125], SMOC2 [126], SPHK1 [127], FOLH1 [128], CYP2C8 [129], CD163 [130], DIRAS3 [131], OSMR (oncostatin M receptor) [132], POSTN (peri...…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes trigger downstream responses related to CCL2, such as the activation of MCP-1-induced protein-1 and the expression of IL-1 and TNF genes, which promote inflammation through the interaction of CCL2 with CCR2. 47,48 CCL2 activates the downstream target P2X4R, which has a dual effect on the progression of ischemic stroke. On the one hand, the production of proinflammatory cytokines is associated with P2X4R, and, on the other hand, P2X4R + cells produce BDNF, which contributes to the recovery of ischemic stroke.…”
Section: Inflammatory and Anti-inflammatory Roles Of Monocytes In Isc...mentioning
confidence: 99%
“…59,60 CCL2 production is mediated by many cytokines, including IFNγ, IL-1/4/6, and TNFα. 47,61 CCL2 is produced by astrocytes and microglia, under anoxic conditions, which are induced by HIF-1. 6,7 CCL2 has three domains, the most important being the N-terminal domain, which determines the affinity of CCR2 binding, as demonstrated in an experiment using MCP-1/3 chimeras.…”
Section: Ccl2/ccr2mentioning
confidence: 99%
“…However, targeting the specific steps of inflammation within the infarcted myocardium may be beneficial for patients with MI who have localized inflammation within the infarcted tissue. Recently introduced therapies targeting the recruitment or polarized macrophages within the infarcted tissue, such as antibodies against chemokines or the cytokines involved in these processes (e.g., targeting the CCL2/CCR2 axis), have shown promising results in preclinical studies [ 10 , 21 , 22 ].…”
Section: Role Of Inflammation In Myocardial Infarctionmentioning
confidence: 99%
“…Nevertheless, the effectiveness of targeted immunotherapy strategies needs to be improved, and strategies sharing specific targets show conflicting results. Many recent preclinical studies have also focused on modifying monocyte responses or targeting the CCL2/CCR2 axis to suppress monocyte-trained immunomodulators after MI inflammation [ 21 , 22 ]. Applying the anti-inflammatory effect of the Trem2 gene could be a new therapeutic strategy for treating MI [ 60 ].…”
Section: The Role Of Trem2 As a Therapeutic Target And Future Directionmentioning
confidence: 99%